Cyclosporine-A-Based Immunosuppressive Therapy-Induced Neurotoxicity: A Case Report - Teimouri, Ali (Open Access Emerg Med, 2020)
Cyclosporine-A (CsA) and ﻿mycophenolate mofetil are immunosuppressive drugs used for the prevention of transplant rejection. Various clinical studies have been performed on different forms of CsA neurotoxicity, including tremor, paresthesia, confusion, ataxia, neuralgia, hemiplegia, occipital seizures, and transient cortical blindness. Mycophenolate is associated with several neurological side effects including headache, insomnia, dizziness, depression, confusion, hypertonia, and paresthesia. A 31-year-old male with a history of kidney transplantation was treated with CsA and ﻿mycophenolate mofetil, for 18 years. He had been referred to the ﻿emergency ﻿department with complaints of generalized tonic-clonic seizure for 1 minute and 15 minutes of the post-ictal phase. Almost all laboratory tests including cerebrospinal fluid analysis were within normal limits. Brain MRI findings were compatible with CsA-based neurotoxicity. The patient’s symptoms and MRI findings improved on decreasing CsA to the minimum dose. CsA neurotoxicity is more common in intravenous therapy, early days of CsA administration, P450 inhibitors administration, and following liver transplantation. MRI findings in CsA neurotoxicity include signal changes in the cerebral cortex and juxtacortical white matter of the occipital lobes, temporal, parietal, and frontal lobes. Every year, many solid organ transplantations are performed. Many of these patients received CsA-based regimens for the prevention of rejection. Therefore, it is necessary to consider CsA neurotoxicity in suspected patients.